Análise das práticas em um Centro de Atenção Psicossocial (CAPS) - Tabuti, Rejane Cristina Teixeira (2013)
This research aims to analyze the practices in a Psychosocial Care Center in the metropolitan region of Curitiba, which caters to people with mental disorders and reflect upon the psychiatric and psychosocial paradigms present. The participants were 13 workers CAPS, 10 users and 8 family. Through consulting the Institutional Therapeutic Project of service and monthly report, we designed a table with description of the activities undertaken. In collecting data, semi-structured interviews were used with workers, and focus groups with users and families. The interviews were analyzed to seize data that related to the practices described. Through their perceptions about practices, we observed the coexistence of psychiatric and psychosocial paradigms, which indicates the need for continuous reflection and the analysis of changes in the daily lives of users served by the service, seeking to achieve the consolidation of the Reformation Psychiatry.